The Influence of Career Development Program Design and Evaluation on Employee Satisfaction of Tourism Educational Institutions at SMK Negeri 3 Tabanan - PUTRA, I Gede Dharma; KOMALASARI, Yeyen (PT Batara Swastika Harati, 2023)
This research examines the satisfaction and career development level of employees of tourism education institutions at SMK Negeri 3 Tabanan. The population in this study were all employees of tourism education institutions at SMK Negeri 3 Tabanan. Quantitative research produces data in various numbers and can generally be analyzed using descriptive or inferential statistics. Several of these variables were then translated into several indicators, which became the basis for statements in the questionnaire, which were later distributed and answered by 32 research respondents. The evaluation of career development programs has a positive and significant effect on the job satisfaction of tourism education employees at SMK Negeri 3 Tabanan. Data analysis shows that the t-count value is 3.734, while the t- table is 1.69. Thus, there is a partial and significant positive influence between the evaluation of career development programs on the job satisfaction of employees of tourism education institutions at SMK Negeri 3 Tabanan. Career development programs and evaluation of career development programs have a positive and significant effect on the job satisfaction of employees of tourism education institutions at SMK Negeri 3 Tabanan. The results of the F test showed that the Fcount value is 13.787 while the Ftable is 3.33. Thus, there is a simultaneous influence between career development program design and career development program evaluation on the job satisfaction of employees of tourism education institutions at SMK Negeri 3 Tabanan.